Midgut Atresia: Diagnostic and Management Challenges From Northern Tanzania. (December 2022) - Lodhia, Jay; Chipongo, Hilary; Mathew, Beatrice; Msuya, David; Chugulu, Samwel; Philemon, Rune
Intestinal obstruction is one of the most common surgical emergencies in the neonatal period. Early diagnosis is vital for proper management and good outcome. Intestinal obstruction can be divided into high, for example, duodenal atresia and jejunal atresia, or low, for example, ileal atresia, colonic atresia, and Meckel's diverticulum. The most common cause of intestinal obstruction in neonates is midgut atresia. Surgical correction is needed and is a challenge in the developing countries where there is lack of pediatric surgeons, anesthesiologists, and intensive care. More research and data is also needed across countries to show the uneven distribution of the available resources.